High-Speed GMAW and Laser GMAW Hybrid Welding of Steel Sheet - Harris, I. D. (Cranfield University, 2009)
Arc welding is the most widely used set of joining technologies in industry today. The automotive tier supplier network and light manufacturing are significant users of arc welding, particularly gas metal arc welding (GMAW) and pulsed GMAW (GMAW-P). For sheet metal welding the majority of welds are single pass fillet welds on T-butt, lap, or edge joints. A fundamental problem and limitation to the use of higher travel speeds in GMAW is the phenomenon of weld bead humping, a weld profile defect with a wavelike profile to the weld bead that has peaks and troughs in the longitudinal direction. Cont/d.